ANALISIS PENGARUH MINAT PELAJAR AKUNTANSI TERHADAP PROFESI AKUNTAN DI KOTA BATAM - Budi Chandra; Pinky Riani S (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to understand the effect of student interest on the accounting profession in Batam City. The dependent variable used is the accounting profession, while the independent variables are the negative attitude of accountants, the image of the accounting profession, perceived behavioral control, accountant job requirements and college reputation. The analytical method used to test the relationship of each independent variable to the dependent using Structural Equation Modeling (SEM) regression. The results of the study concluded that the image of the accounting profession, accountant job requirements and college reputation had a significant positive effect on the accounting profession that would be chosen by accounting students in Batam City, while the negative attitudes of accountants and perceived behavioral control had no significant effect.